Distribusi dan Eksibisi Film Alternatif di Yogyakarta, Resistensi atas Praktek Dominasi Film di Indonesia - Budi Dwi Arifianto; Fajar Junaedi (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2014)
This study attempts to describe the strategy and the distribution pattern of “Ngamen” cinema in Yogyakarta. The research methodology that is used is qualitative descriptive with data collection through in-depth interviews involving an offender of cinema in Yogyakarta, the literature study and relevant documents. This study found that was the film community as the basis distributor of short film or alternate in Yogyakarta. This community can come from campus and outside campus. In a line distribution filmmaker of Yogyakarta play the movie from one place to another place by the festival playback on a campus and screening outside campus. The development of the internet technology made it easier for in search of a sac culture and decent it can be used the movie. Through the internet on filmmaker of Yogyakarta looking for another film community who were willing to roll the the movie.